Evaluation of influence of two different catalysts on the pyrolysis of laurel (Laurus nobilis L.) extraction residues. Issue 3 (1st February 2016) - Ertaş, Murat; Hakkı Alma, M.
ABSTRACT: Laurel extraction residues with zeolite and alumina catalysts were pyrolyzed in a fixed-bed reactor with a constant heating rate of 10°C min –1 . The final pyrolysis temperature and sweep gas flow rate were kept constant at 500°C and 100 ml min –1 in all of the experiments, respectively. The influence of catalysts and their ratio (10, 20, 30, 40, and 50% w/w) on the pyrolysis conversion and product yields were investigated in detail. The physicochemical properties of the catalytic bio-oil were determined and compared to those of non-catalytic bio-oil. The catalytic bio-oils were examined using some spectroscopic and chromatographic techniques.